Applicability and Variability of Chemical Weathering Indicators and Their Monsoon-Controlled Mechanisms in the Bay of Bengal - Li, Jingrui; Liu, Shengfa; Shi, Xuefa; Zhang, Hui; Cao, Peng; Li, Xiaoyan; Pan, Hui-Juan; Khokiattiwong, Somkiat; Kornkanitnan, Narumol (Frontiers in Earth Science, 2021)
To help understanding the potential relationship between chemical weathering and Indian summer monsoon (ISM) since the last glacial period a gravity core (BoB-56) was retrieved from the central Bay of Bengal (BoB). The data of chemical weathering indexes used in this study showed general synchronicity with the regional monsoon precipitation and temperature record on processional scale, indicating existence of a general “climate-driving weathering” pattern. Corresponding to alteration of “warm-cold” period during the last deglaciation, obvious simultaneously alteration of “peak-valley” values of the chemical weathering and terrestrial input proxies’ record support our hypothesis that monsoon climate driving chemical weathering on the millennial scale. However, a contradiction occurred during the Holocene period, when monsoon precipitation and temperature rose to a higher level, while the chemical weathering indexes unanimously decreased to a lower values. In this study, we discussed the applicability of chemical weathering indexes in the BoB during the Holocene period. Besides the possible weakened monsoon during 6-3 ka, recorded by the stalagmite δ18O and SST reconstruction results in the northeastern Indian Ocean, other factors were responsible for this phenomenon, including the geochemical composition, grain size effect, and distinction between the mountain high land and floodplain low land. The CIA (chemical index of alteration), WIP (weathering index of Parker), and αAlNa records, during the last glaciation, indicated the presence of a “climate-driving weathering” pattern on processional and millennial scales. While, during the Holocene, they failed to reflect the chemical weathering dynamics of the source area. Indeed, a mixture of physical erosion and chemical weathering seems to be representative of the chemical weathering dynamics in the area. Our findings emphasized on the tight connections between the chemical weathering evolution and global-regional climate conditions around the BoB, implying possible ISM-controlled mechanisms during different time scales.